EFFECT OF ENVIRONMENTAL, SOCIAL, GOVERNANCE (ESG) DISCLOSURE AND DISPARITY ON FINANCIAL PERFORMANCE AND FIRM VALUE - Ilham Azhar Effendi; Eka Pria Anas (RADJA PUBLIKA, 2026)
This study examines the effect of Environmental, Social, and Governance (ESG) disclosure and rating disparity on the financial performance and firm value of companies listed on the Indonesia Stock Exchange. The sample includes 45 companies from the ESG Leaders Index during 2019–2023. ESG disclosure is measured using scores from Bloomberg and Refinitiv, while disparity is calculated from the difference between both. Financial performance is measured by Return on Assets (ROA), and firm value by Tobin’s Q. Using panel data regression with a fixed effect model, the results show Bloomberg’s ESG score has a positive impact on ROA, while Refinitiv’s score has a negative effect. Both ESG scores negatively affect firm value. Surprisingly, ESG disparity shows a positive correlation with firm value. These findings highlight the need for harmonized ESG standards and caution for investors relying on ESG ratings.